Rancang Bangun Mesin Pemotong Adonan Kerupuk Rambak Tepung Guna Meningkatkan Kapasitas Produksi - Prastyo, Ilham Dwi; Putu Eka Dewi Karunia Wati (Fakultas Teknik UMRI, 2024)
In this era of progress in all sectors, which has an impact on the industrial sector in Indonesia, causing increasingly high competition. This research uses the Make to Order (MTO) and Make to Stock (MTS) production systems. The method used in this research contains stages that involve collecting data and information through interviews, observation, library studies. Based on the improvements that have been obtained, production capacity can also be increased, which was previously in line with demand. This happens because there is an automatic cracker dough cutting machine, so there is no excessive workload caused by manually cutting cracker dough.